Generation Control of ZnO Nanoparticles Using a Coaxial Gas-Flow Pulse Plasma Ar/O2 Plasma. (7th September 2015) - Shirahata, Hiroki; Iizuka, Satoru
Abstract : Generation of ZnO nanoparticles was investigated using a coaxial gas-flow pulse plasma. We studied how zinc atoms, sputtered from a zinc target, reacted with oxygen in a plasma and/or on a substrate to form ZnO nanoparticles when the discharge parameters, such as applied pulse voltage and gas flow rate, were controlled in an O2 /Ar plasma. The formation processes were estimated by SEM, TEM, and EDX. We observed many ZnO nanoparticles deposited on Si substrate. The particle yield and size were found to be controlled by changing the experimental parameters. The diameter of the particles was typically 50–200 nm.